Photographic grading to evaluate facial cleanliness and trachoma among children in Amhara region, Ethiopia. - Ramoncito L Caleon; Fisseha Admassu; Solomon Aragie; Dagnachew Hailu; Adane Dagnew; Taye Zeru; Dionna M Wittberg; Isabel J B Thompson; Seid Abdu; Social Beyecha; Tibebe Birhanu; Habib Getachew; et al. (Public Library of Science (PLoS), 2024)
Background Promotion of facial cleanliness is recommended for the elimination of blinding trachoma, largely because of observational studies that have found an association between various measures of facial uncleanliness and trachoma. However, when a field grader assesses both facial cleanliness and trachoma, associations may be biased. Assessment of photographs of the face and conjunctiva by masked graders may provide a less biased estimate of the relationship between facial cleanliness and trachoma. Methods Face photographs, conjunctival photographs, and conjunctival swabs were obtained on a random sample of 0-9-year-old children from each of 40 communities in Amhara region, Ethiopia. Face photographs were assessed for the presence of seven measures of an unclean face (i.e., wet nasal discharge, dry nasal discharge, wet ocular discharge, dry ocular discharge, food, dust/dirt, and flies) by three independent masked photo-graders. Conjunctival photographs were similarly graded in a masked fashion for signs of clinically active trachoma. Conjunctival swabs were processed for Chlamydia trachomatis DNA. Results Of 2073 children with complete data, 808 (39%) had evidence of clinically active trachoma, 150 (7%) had evidence of ocular chlamydia infection, and 2524 (91%) had at least one measure of an unclean face. Dry ocular discharge had the strongest association with clinically active trachoma (age- and sex-adjusted prevalence ratio [PR] 1.4, 95% CI 1.2-1.6) and ocular chlamydia infection (PR 1.9, 95%CI 1.3-2.9), although significant associations were observed between each of the measures of facial uncleanliness and trachoma. Conclusions Masked assessment of face and conjunctival photographs confirmed prior observational studies that have noted associations between various measures of facial uncleanliness and trachoma. The causal relationship between facial uncleanliness and trachoma is unclear since many features used to measure facial cleanliness (e.g., ocular discharge, nasal discharge, and flies) could be consequences of antecedent ocular chlamydia infection. Trial registration NCT02754583, clinicaltrials.gov.